The multifaceted nature of diabetic erectile dysfunction: uncovering the intricate mechanisms and treatment strategies - Ma, Jianxiong; Chen, Yihao; Si, Yuhe; Qian, Jiahua; Wang, Chenxi; Jin, Juan; He, Qiang (Frontiers in Endocrinology, 2024)
Background: One of the most common complications of diabetes mellitus is diabetic erectile dysfunction (DMED), a condition that has grown more common in recent years and has a significant impact on patients' daily lives. The complicated pathophysiological changes of DMED, involving vascular, neurological, muscular, and endocrine variables, have not been well addressed by any one treatment technique, and no widely approved treatment strategy has been developed. Aim: The objective of this study was to thoroughly examine the complex nature of the pathogenic mechanism of DMED and discover new therapeutic approaches that could improve DMED symptoms. Methods: Studies and review articles from the past 10 years were considered. Results: The pathogenesis of DMED encompasses vascular dysfunction, endothelial cell damage, cavernous smooth muscle defects, neurological dysfunction, endocrine/metabolic factors, leukomalacia fibrosis, and psychosocial factors, elucidating complex interplay among the mechanisms underlying DMED. It underscores the need of integrating traditional herbal medicine, energy-based medicine treatments, and advanced techniques like stem cell and gene therapy to enhance therapeutic outcomes. Furthermore, it expresses optimism on the therapeutic potential of new nanobiomaterials in DMED. Conclusion: Through integrating a complete description of DMED etiology and current therapy methods, this work offers a helpful resource for researchers, doctors, and patients dealing with this difficult condition.